Promotion of maize growth using endophytic bacteria under greenhouse and field conditions - Lobo, Laiana Lana Bentes [UNESP]; dos Santos, Roberta Mendes [UNESP]; Rigobelo, Everlon Cid [UNESP] (Southern Cross Publishing, 2019)
The effect of Bacillus subtilis isolates before being used as inoculants is very important. They present various impacts on promotion and characteristics of plant at different stages of growth. This experiment was carried out on maize under greenhouse conditions with eleven treatments of endophytic bacteria and three repetitions. The better isolates under greenhouse conditions were used in the field experiment with four best treatments and six replicates. The traits evaluated under both conditions were height, shoot and root dry matter, and the nitrogen and phosphorus content in the plant and soil and the total number of bacteria in the soil. Under greenhouse conditions, the groups that received Bacillus spp. showed higher amount of soluble phosphorus and total numbers of bacteria compared to control. Under field condition, isolate BS-290 increased the nitrogen and phosphorus concentrations in shoot dry matter, phosphorus concentration in dry soil and the total number of bacteria in the soil, compared to the control. Isolate BS-320 increased the phosphorus concentration in plants and maize yield, which strongly suggests its use as a biological inoculant for maize crops. BS-248, BS 290 and BS-320 isolates promoted the highest maize growth, compared to the other isolates. The results showed that Bacillus subtilis isolates that promote plant growth did not increase similar traits in all plants and the behavior has been highly isolate-dependent. This finding shows that the isolates had a preference and certain specificity on each individual trait.
Keywords: Bacillus subtilis; Inoculation; Nitrogen-fixing; Phosphorus solubilization